29-6x=5(1-6x)

Simple and best practice solution for 29-6x=5(1-6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 29-6x=5(1-6x) equation:



29-6x=5(1-6x)
We move all terms to the left:
29-6x-(5(1-6x))=0
We add all the numbers together, and all the variables
-6x-(5(-6x+1))+29=0
We calculate terms in parentheses: -(5(-6x+1)), so:
5(-6x+1)
We multiply parentheses
-30x+5
Back to the equation:
-(-30x+5)
We get rid of parentheses
-6x+30x-5+29=0
We add all the numbers together, and all the variables
24x+24=0
We move all terms containing x to the left, all other terms to the right
24x=-24
x=-24/24
x=-1

See similar equations:

| 3x+2=x–3 | | -s+2s-3=4 | | (–9+5t)(–6)= | | 2(x–8)=–22 | | 20/8=x/16 | | (4x-18)+(3x+4)=180 | | 1.20x+3.60=9.6 | | 12/8=x/12 | | -156=12x | | 2x=5=13 | | -11+5n=5+7n | | 4g+4g=16 | | 5x/3+13=-2 | | -5x+4=-x+16 | | 2x+16=5x-17=11x | | 181=-y+102 | | 2x+14.5=21.5 | | -4x-8x=-144 | | -4n+9=+4n+9 | | 0.29x-7.34=1.64+0.79x | | -49x+8)-11=3-26 | | 2x+3−5x=3 | | (27)3^2-2*3+u=(3^3-3*8)(2)+u | | -4n+9=-4n+9 | | 2x+16=5x-17=11 | | g-2/4=-3 | | 2+6a-6a=3a+2-6 | | 7x+2=–3x–5 | | 7(8-8y)+10=-270 | | x/42=15/35 | | -14=p11 | | -4n+9=+-4n+9 |

Equations solver categories